The use of blog to facilitate development in writing among ESL tertiary-level learners at UiTM Seri Iskandar, Perak / Nur Hani Laily Ramli - Ramli, Nur Hani Laily (2013)
Conflicts in writing among second language learners have driven many researchers to conduct studies to explore this field. This study is to investigate deeply on the use of blog to facilitate the development in writing among ESL tertiary-level learners in Malaysia. Twenty Malay ESL tertiary-level learners enrolled in English for Academic Purposes (BEL311) at Universiti Teknologi MARA Perak, Seri Iskandar campus are selected as subject for this investigation. The researcher employs both qualitative and quantitative approaches which involved questionnaires, observations on learners’ blogs and interview. Questionnaires were analyzed using descriptive and inferential statistics. The finding of this study indicated that there was an increment in learners’ overall development in writing after they involved in blogging activities for fourteen weeks. In general, the study revealed that, rather than improving learners’ development in writing; it contributed more towards the improvement in learners’ writing skill.